SELF-HELP SKILLS OF PUPILS WITH INTELLECTUAL DISABILITY: A QUASI EXPERIMENTAL RESEARCH - Jacob, Udeme Samuel; Pillay, Jace; Olukanni, Amos Olajuwon; Ebulum, Genevieve Chimaoge (Jurnal Tatsqif, 2024)
Children with intellectual disabilities risk becoming physically and emotionally dependent on adults because they cannot care for themselves. This study examined how play ways, social stories, and parents' socioeconomic status affect self-help skills among pupils with intellectual disability. This study used a 3 x 2 factorial design as part of a quasi-experimental pretest-posttest and control group research design. Purposive sampling was used to select thirty pupils with intellectual disability (N = 30, M = 13, F = 17, Mean age = 12.3) from three government-owned primary schools. The play way and social story method instructional packages on self-help skills were two treatment packages. Performance Assessment of Self-care Skills (PASS) and parental socioeconomic scales was used to collect data. Analyses of covariance (ANCOVA) and marginal mean scores were conducted at a significance level of 0.05 to test for the significance of the data collected. Self-help skills of pupils with intellectual disability were significantly affected by treatment [F (1,10) = 2.866 p > 0.05; partial ?2 = 0.193], while the adjusted Marginal Mean revealed that play way was the most effective treatment. Furthermore, the result demonstrates that parents' socioeconomic status substantially enhanced the self-help skills of pupils with intellectual disability. A high parent's socioeconomic status influenced participants' self-help skills more. Results from the study suggest that children with intellectual disability can benefit from a play-way approach, social stories, and parental socioeconomic status.